Activity test cream anti aging extract ethanol 70% star fruits leaves (Averrhoa bilimbi l.) on skin new zealand rabbit backs exposed to UV-A light - Puspitasari, Iliananda; Saraswati, Maulita; Sari, Gigih Kenanga (Journal of Health Management and Pharmacy Exploration, 2025)
Skin is an organ that protects humans from external influences. Damage to the skin can interfere with human health and appearance. One of the most feared things is premature aging, the main cause of skin aging and malignant melanoma is the entry of ultraviolet (UV) rays from the sun. One of the plants, namely starfruit leaves, has antioxidant content that can change or reduce free radicals and also as an anti-free radical such as flavonoids, saponins, alkaloids, and tannins. Cream can be used by applying it to the skin of the face to prevent anti aging. Objective: To determine the activity of anti-aging cream of 70% ethanol extract of starfruit leaves (Averrhoa bilimbi L.) on the back skin of New Zealand rabbits exposed to UV-A light. Methodology: Extract starfruit leaves using the maceration method with 70% solvent and make a cream preparation to test anti-aging activity with concentrations of 3%, 5%, and 7%. Results: Formulation 3 with a concentration of 7 % of starfruit leaf extract cream can provide optimal effects as an anti-aging agent when exposed to UV-A rays, seen from the average value which is almost the same as the positive control.